Diseño de un sistema de instalación y distribución eléctrica de baja tensión para luminarias y tomacorrientes en áreas comunes para el condominio jardines de Santorini en Villavicencio (2024)
This preliminary project proposes the design and development of an efficient and safe electrical system for lighting and outlets in the common areas of a condominium. The problem being addressed is the lack of adequate and reliable electrical infrastructure that meets the lighting and connectivity needs in shared spaces. The objective is to create an electrical system that complies with current regulations, that is based on technical concepts and international standards, and that implements innovative approaches to optimize energy efficiency, reduce operating costs and promote sustainability. The methodology consists of applying the principles of electrical design, performing calculations and simulations, selecting the appropriate materials and equipment, and preparing the corresponding plans and diagrams. The scope of the preliminary project covers the common areas of the condominium, such as hallways, stairs, social rooms, parking lots, green areas, etc. The expected results are a functional and safe electrical system that provides adequate lighting and connectivity in the common areas of the condominium. KEYWORDS: electrical system, regulatory electrical design, current, lighting, connectivity, energy efficiency, sustainability.